Formulasi Strategi Bisnis Distribusi Tekstil UD. XYZ Menggunakan Model Diamond Strategy - Hidayati, Syafrina; Munir Sukoco, Badri (Rifa'Institute, 2023)
UD. XYZ is a business engaged in the distribution of textiles since 1995. UD. XYZ distributes its products to B2B (Business to Business), namely convection manufacturers and B2C, namely end consumers. In 2020 and 2021 UD. XYZ experienced a decrease in revenue and market share due to the impact of the pandemic. This study aims to formulate a textile distribution business strategy that fits UD. XYZ. This study uses an analysis of the five main elements of the diamond strategy from Hambrick & Fredickson. This study uses a qualitative method. Data collection techniques using interviews, observation and document study. The results of this study are the analysis of the five main elements of the diamond strategy, namely: (1) Arena, covering answers regarding product categories for convection needs, B2B and B2C market segments, East Java geographical area, computerized inventory system technology, finance and digital marketing, and efficiency value creation; (2) Vehicles, through partnerships and internal development; (3) Differentiators, in terms of image quality guaranteed at competitive prices, in terms of customization of cloth cutting services, in terms of competitive and affordable prices, in terms of styling different qualities, in terms of product availability, best seller ready stock products. (4) Staging is divided into short, medium and long term; (5) Economic Logic with cost effectiveness.